Correlation between the Magnetic and DC resistivity studies of Cu substituted Ni and Zn in Ni-Zn ferrites - Parajuli, D.; Murali, N.; Samatha, K. (BIBECHANA, 2022)
Cu substituted Ni0.5-xCuxZn0.5Fe2O4 (x = 0, 0.05, 0.1, 0.15 and 0.2) samples is synthesized using the sol-gel auto-combustion process. They have a cubic spinel structure with crystallite size in the range of 29.01–42.68 nm. The increment in the copper content increases the DC conductivity. The electrical resistivity decrease with an increase in the temperature i.e. it has a negative temperature coefficient with resistance similar to semiconductors. The remnant ratios R obtained from VSM show their isotropic nature forming single domain ferrimagnetic particles. The results are compared with Ni0.5CuxZn0.5-xFe2O4 (x = 0 to 0.25). The resultant material Cu substituted Zn is more significant than that of Ni as indicated by its results and previous literature. BIBECHANA 19 (2022) 61-67